MONITORING TINGKAT KEKRITISAN LAHAN AKIBAT PERUBAHAN TUTUPAN LAHAN MENGGUNAKAN CITRA SENTINEL 2A DI KECAMATAN BANYAKAN, KABUPATEN KEDIRI: Monitoring the Criticality Levels of Land Using Sentinel 2A Imagery in Banyakan Subdistrict, Kediri Regency (Jurnal ForestrIndo, 2025)
Banyakan Subdistrict, Kediri Regency, is experiencing pressure from the conversion of agricultural land into intensive infrastructure development, which potentially leads to land degradation. This study aims to analyze land cover and monitor land criticality levels in Banyakan Subdistrict for the years 2017 and 2024 using Sentinel-2A imagery. Land cover classification were analyzed using the maximum likelihood classification method. Land criticality was assessed by five parameters: land cover, slope gradient, erosion hazard level, land productivity, and land management. The results show that mixed gardens dominate the land cover classes. There was an increase of 82.20 hectares in open land, mainly due to airport construction. This land cover change has resulted in an increase in land criticality levels, indicated by an expansion of the critical class by 0.91 hectares and the potentially critical class by 6.97 hectares in protected areas. In agricultural cultivation areas, there was an increase in the non-critical class by 994.14 hectares. Meanwhile, the most significant decrease occurred in production areas within the potentially critical class, which declined by 326.91 hectares. Nevertheless, there was a relatively large increase of 306.61 hectares in the slightly critical class within production areas.